2018
DOI: 10.1002/asjc.1939
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Control for Markovian Jump Systems with Generalized Switching

Abstract: In this paper, the sliding mode control (SMC) problem for continuous-time Markovian jump systems (MJSs) is considered, in which the transition rate matrix (TRM) is partially unknown and uncertain. Firstly, the sliding mode surface S(t) = 0 is designed, which is mode-dependent. Therefore, ℒ S(t) is used instead ofṠ(t) in the SMC algorithm. Via adopting a linear matrix inequality (LMI) approach, sufficient conditions are proposed to ensure that the reduced order system is exponentially stable in mean square. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Now, by means of P i Pi = I, the inequalities ( 13) are formulated to be the inequalities (10). Furthermore, it gets from Ma and Xiong [14] that P i Pi = I is equivalent to the rank constraints (11). The proof is achieved.…”
Section: Design Of Stabilizing Tpmmentioning
confidence: 95%
See 1 more Smart Citation
“…Now, by means of P i Pi = I, the inequalities ( 13) are formulated to be the inequalities (10). Furthermore, it gets from Ma and Xiong [14] that P i Pi = I is equivalent to the rank constraints (11). The proof is achieved.…”
Section: Design Of Stabilizing Tpmmentioning
confidence: 95%
“…Some typical engineering applications of MJLSs can be found in the wind turbine and networked control system [3][4][5]. Meanwhile, some existing results on study-ing the stability analysis and control/filtering issues of MJLSs have been reported in several studies [6][7][8][9][10][11] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Sliding mode control (SMC), as a powerful robust control strategy in handling external disturbances and parameter uncertainties, has been widely employed to different kinds of systems [16][17][18][19][20][21][22][23]. The key idea of SMC is to utilize a discontinuous control to drive the system state trajectories into the bounded sliding mode region and stay there in the subsequent time.…”
Section: Introductionmentioning
confidence: 99%
“…The switching among the modes is governed by a Markov process which has discrete and finite state space. Therefore, it could model many dynamic systems [19–23]. In this class of systems, transition rates are the major factors in the jump process.…”
Section: Introductionmentioning
confidence: 99%